1991
DOI: 10.1113/jphysiol.1991.sp018373
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pH changes on human and ferret detrusor muscle function.

Abstract: 1. The effects of altering extracellular pH on the electrically evoked contractions of ferret and human bladder (detrusor) smooth muscle have been investigated. pH was varied by changing superfusate PCO2 or NaHCO3 concentration. Acidosis increased force when superfusate PCO2 was raised but decreased force when the NaHCO3 concentration was reduced. 2. Intracellular pH (pHi) in isolated ferret detrusor cells was measured separately by epifluorescence microscopy. Extracellular pH changes caused by altering superf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
1

Year Published

1992
1992
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 28 publications
5
38
1
Order By: Relevance
“…Actions of H¤ on detrusor smooth muscle A pHé value of 7·10 in guinea-pig detrusor myocytes (Table 1) is similar to that reported for human and ferret detrusor myocytes (Liston et al 1991;Fry et al 1994b). The sustained nature of the pHé change when superfusate PCOµ was altered and the lack of effect upon changes to superfusate [NaHCO×] at constant PCOµ measured in this study is in contrast to observations in some other smooth muscles (Aickin & Brading, 1984;Aalkjòr & Cragoe, 1988;Austin & Wray, 1993) and may reflect different pH-regulating mechanisms or surface membrane permeability to H¤ between detrusor and these other muscles.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Actions of H¤ on detrusor smooth muscle A pHé value of 7·10 in guinea-pig detrusor myocytes (Table 1) is similar to that reported for human and ferret detrusor myocytes (Liston et al 1991;Fry et al 1994b). The sustained nature of the pHé change when superfusate PCOµ was altered and the lack of effect upon changes to superfusate [NaHCO×] at constant PCOµ measured in this study is in contrast to observations in some other smooth muscles (Aickin & Brading, 1984;Aalkjòr & Cragoe, 1988;Austin & Wray, 1993) and may reflect different pH-regulating mechanisms or surface membrane permeability to H¤ between detrusor and these other muscles.…”
Section: Discussionsupporting
confidence: 71%
“…The sustained nature of the pHé change when superfusate PCOµ was altered and the lack of effect upon changes to superfusate [NaHCO×] at constant PCOµ measured in this study is in contrast to observations in some other smooth muscles (Aickin & Brading, 1984;Aalkjòr & Cragoe, 1988;Austin & Wray, 1993) and may reflect different pH-regulating mechanisms or surface membrane permeability to H¤ between detrusor and these other muscles. nerves embedded in the tissue or by direct electrical stimulation of the muscle (Liston et al 1991). In this study, extracellular acidosis was negatively inotropic, a finding similar to that in cardiac and several other smooth muscles (Wray, 1988;Orchard & Kentish, 1990); however, intracellular acidification increased the force of phasic contractions.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Fry Division of Physiology, UMDS, London SE1 7EH Hydrodistension of the bladder reduces blood flow to the organ (Siroky et al 1990). Changes to intracellular and extracellular pH have profound effects on detrusor smooth muscle contractility (Liston et al 1991) and in man urodynamic intravesical pressure measurements have been shown to be affected by the pH of the filling solution (Sethia & Smith, 1987). The aim of this present study was to determine whether intramural pH changes accompanied bladder wall ischaemia during bladder filling.…”
mentioning
confidence: 99%